Meningkatkan Keterampilan Membaca Permulaan Pada Mata Pelajaran Bahasa Indonesia dengan Model Pembelajaran Make A Match Berbantuan Flash Card di Kelas 2B SD Negeri 1 Sumbang - Novia Isnandari; Pamujo Pamujo (Departement of Mathematics Education, 2024)
This research is based on the low early reading skills of students in Grade 2B of SD Negeri 1 Sumbang Banyumas. A solution to minimize this problem is to apply the make-a-match learning model assisted by flash cards. This study aims to improve students' early reading skills in Indonesian language subject, particularly for students in Grade 2B, using the make-a-match learning model assisted by flash cards. Classroom Action Research (CAR) was chosen for this research, consisting of 2 cycles. Each cycle includes two meetings and four stages: planning, implementation, observation, and reflection. This study selected Grade 2B as the research subject, with 31 students. Data collection techniques included tests, observation, and documentation. The results of this study showed that the early reading skills of students in cycle I were less effective, with a completeness percentage of 74.20%. There was a significant improvement in cycle II, with a completion percentage of 83.88%. Thus, it can be concluded that using the make-a-match learning model assisted by flashcards can improve the early reading skills of students in Grade 2B of SD Negeri 1 Sumbang.